Pertumbuhan dan Produksi Jintan Hitam pada Beberapa Komposisi Media Tanam dan Interval Penyiraman - Mardisiwi, Ririh Sekar; Kurniawati, Ani; Sulistyono, Eko; Fardidah, dan Didah Nur (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2018)
Black cumin plant ‘Habatussaudah’ (Nigella sativa L.) is a new introduced plant in Indonesia, therefore it is necessary to study cultivation method in order to produce high yield of good quality. This study was aimed to evaluate the growth of black cumin on different composition of media and watering intervals. The experiment was conducted at Sarongge Experimental Station, Cipanas, West Java (1,117 m asl) from June to October 2016. The experiment used a randomized block design with three replications. The treatment consisted of two factors, namely the composition of the planting media and the watering interval. The composition of planting medium consisted of  soil only (M0), soil: manure (1:1, v/v) (M1), soil: manure: rice-hull charcoal (1: 1: 1) (M2), soil: manure: rice-hull charcoal (2: 1: 1) (M3). The watering interval consisted of 4 levels, i.e., watering every 4, 7, 10 and 13 days. The results showed that soil with manure and or rice-hull charcoal increased the growth of vegetative, generative and production of black cumin 1.5 g per plant. Watering at intervals of 4 and 7 days produced better plant growth than those of  watering with longer intervals. Keywords: Habbatusauda, high altitude, introduced plant, medicinal plant, tropical area